WOMEN’S LANGUAGE POLITENESS IN FACEBOOK STATUS UPDATES A CRITICAL DISCOURSE ANALYSIS OF GENDERED DISCURSIVE PRACTICES - Elita Modesta Sembiring; Rahmah Fithriani; Pardi Pardi (Universitas Putera Batam, 2026)
This study uses Critical Discourse Analysis (CDA) to examine women's language politeness in Facebook status updates. Fewer studies have looked at how politeness functions as a gendered discursive practice in digital communication, despite the fact that it has historically been studied as a pragmatic strategy for reducing face-threatening acts. Drawing on Brown and Levinson’s politeness theory and Fairclough’s three-dimensional model of CDA, this qualitative study analyzes 50 Facebook status updates posted by female users. The findings reveal that women predominantly employ positive politeness, negative politeness, and off-record strategies to maintain social harmony, manage face, and negotiate public self-presentation. At the discursive level, politeness functions as a normative expectation shaping women’s online identities, while at the socio cultural level, it operates as an ideological resource that reproduces gendered norms of emotional labor, relational responsibility, and self-regulation. This study contributes to pragmatics and critical discourse studies by reconceptualizing politeness not merely as an interpersonal strategy but as a socially embedded and ideologically loaded practice in digital discourse. Keywords: politeness, women’s language, Facebook status updates, gender, critical discourse analysis, digital discourse